2017
DOI: 10.1158/0008-5472.can-16-3398
|View full text |Cite
|
Sign up to set email alerts
|

ATM Deficiency Is Associated with Sensitivity to PARP1- and ATR Inhibitors in Lung Adenocarcinoma

Abstract: Defects in maintaining genome integrity are a hallmark of cancer. The DNA damage response kinase ATM is frequently mutated in human cancer, but the significance of these events to chemotherapeutic efficacy has not been examined deeply in whole organism models. Here we demonstrate that bi-allelic Atm deletion in mouse models of Kras-mutant lung adenocarcinoma does not affect cisplatin responses. In marked contrast, Atmdeficient tumors displayed an enhanced response to the topoisomerase-II poison etoposide. More… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 56 publications
6
74
0
Order By: Relevance
“…In the context of KRAS -driven lung adenocarcinoma and PDAC, 2 recent preclinical in vivo studies have highlighted the potential importance of ATR inhibitors. The ATR inhibitor VE-822 displayed selective cytotoxicity in Tp53 -deficient Kras -driven lung adenocarcinoma cells and tumors that lacked Atm expression, whereas the Atm -proficient controls were significantly more resistant [81]. The effects observed with VE-822 were similar to those observed with olaparib, which was employed as a control in these studies [81].…”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 85%
See 4 more Smart Citations
“…In the context of KRAS -driven lung adenocarcinoma and PDAC, 2 recent preclinical in vivo studies have highlighted the potential importance of ATR inhibitors. The ATR inhibitor VE-822 displayed selective cytotoxicity in Tp53 -deficient Kras -driven lung adenocarcinoma cells and tumors that lacked Atm expression, whereas the Atm -proficient controls were significantly more resistant [81]. The effects observed with VE-822 were similar to those observed with olaparib, which was employed as a control in these studies [81].…”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 85%
“…Thus, it has been speculated that it is the HR defect in BRCA1/2 -mutated cancer cells that confers sensitivity to PARP inhibition [73,74]. In line with this concept, further experiments have shown that PARP inhibition is indeed selectively toxic in cancer cells that harbor aberrations in additional HR genes, such as ATM , RAD51 , RAD54 , DSS1 , RPA1 , NBN , ATR , CHEK1 , CHEK2 , FANCD2 , FANCA and FANCC [77,78,79,80,81]. Given that several critical phenotypes that are associated with BRCA1 or BRCA2 deficiency are also detectable in situations where no germline BRCA1/2 mutation can be detected, the term ‘BRCA-ness' has been coined.…”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 99%
See 3 more Smart Citations